Analysis the effect of the fraud triangle on fraud report finance use beneish M-Score model - Harpan, Deddi; Kuntadi, Cris (Universitas Wiralodra, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables . This article reviews the factors that influence financial statement fraud, namely external pressure (pressure), nature of the industry (opportunity) and rationalization (justification), all of which are factors of the fraud triangle, a study of accounting literature using the ability of the beneish m-score. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Pressure has an effect on fraudulent financial statements; 2) Opportunities influence fraudulent financial statements; and 3) Justification has an effect on fraudulent financial reporting. Keywords: Financial Statement Fraud, Pressure, Opportunity and Justification